Formulation Of Lyophilized Membrane Using Cnt/Hap For Soft Tissue Regeneration - Sekhar, Pavithra; Bhargavi, Bhargavi (Journal of Neonatal Surgery, 2024)
Soft tissue regeneration remains a major challenge in regenerative medicine and periodontal therapy. Biomaterial-based scaffolds capable of supporting cellular adhesion, proliferation, and differentiation are essential for effective tissue repair. Carbon nanotubes (CNTs) possess remarkable mechanical strength, electrical conductivity, and nanoscale architecture, making them attractive candidates for tissue engineering applications. Hydroxyapatite (HAp), a calcium phosphate compound similar to the mineral component of bone, is widely used due to its excellent bioactivity and biocompatibility. In the present study, a lyophilized composite membrane composed of CNT and HAp was formulated using sodium alginate as a polymer matrix. The CNTs were acid-treated and dispersed within the alginate solution followed by incorporation of HAp to form a composite scaffold. The resulting membrane was subjected to lyophilization to obtain a porous structure suitable for tissue regeneration. Morphological characterization was performed using scanning electron microscopy (SEM), which revealed a porous and interconnected microstructure favorable for cell attachment. ATR-FTIR spectroscopy confirmed the presence of functional groups associated with CNT, alginate, and HAp within the composite membrane. Cell viability assays demonstrated approximately 96% cell viability, indicating good cytocompatibility of the scaffold. These results suggest that the CNT/HAp lyophilized membrane possesses promising structural and biological properties for soft tissue regeneration and tissue engineering applications..